Aspects of Enlightenment : Social Theory and the Ethics of Truth. - Osborne, Thomas (Taylor & Francis Ltd., 1998)
An account of social theory and the role of enlightenment within it. The most immediate and central topic of such a social theory should be the question of enlightenment. However, the book departs from traditional accounts and it makes a strong argument for the ethical status of enlightenment.